2022
DOI: 10.3389/fcell.2022.1023332
|View full text |Cite
|
Sign up to set email alerts
|

Roles of circular RNAs in the pathogenesis and treatment of pancreatic cancer

Abstract: Circular RNAs are single-stranded RNAs with a covalently closed structure formed by the process of back-splicing. Aberrant expression of circular RNAs contributes to the pathogenesis of a wide range of cancers. Pancreatic cancer is one of the most lethal cancers due to diagnostic difficulties and limited therapeutic options. Circular RNAs are emerging as novel diagnostic biomarkers and therapeutic targets for pancreatic cancer. Moreover, recent advances in the therapeutic application of engineered circular RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…CircRNA typically consists of 100 to 4000 base pairs in length. Instead of a linear shape formed by lncRNA and miRNA, it forms a covalently closed loop structure that links 5 ′ and 3 ′ ends [97]. This unique structure, which lacks free ends, enhances stability and resistance to degradation by RNase R, a 3 ′ to 5 ′ exoribonuclease.…”
Section: Circular Rna (Circrna)mentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNA typically consists of 100 to 4000 base pairs in length. Instead of a linear shape formed by lncRNA and miRNA, it forms a covalently closed loop structure that links 5 ′ and 3 ′ ends [97]. This unique structure, which lacks free ends, enhances stability and resistance to degradation by RNase R, a 3 ′ to 5 ′ exoribonuclease.…”
Section: Circular Rna (Circrna)mentioning
confidence: 99%
“…This unique structure, which lacks free ends, enhances stability and resistance to degradation by RNase R, a 3 ′ to 5 ′ exoribonuclease. Additionally, circRNA is ubiquitously expressed in body fluids such as plasma, saliva, and urine, making it an excellent biomarker for cancer diagnosis [97]. A meta-analysis including six diagnostic studies suggested that circRNA could distinguish PDAC patients from healthy groups, with relatively high AUC, sensitivity, and specificity values of 0.86, 84%, and 80%, respectively [98].…”
Section: Circular Rna (Circrna)mentioning
confidence: 99%
“…(3) Acting as scaffolds for protein complexes leading to mRNA-protein complex formation enhancing mRNA expression and tumour progression. So, they will be a target for different therapies of PC soon (Figure 2) [7,8].…”
Section: Genetics Molecular Alterations Metabolic Changes and Cancer ...mentioning
confidence: 99%
“…The 5-year survival rate after PC diagnosis may reach only 5-11%. However, for the very early diagnosed ones, it may rise to 85% and horribly; for the locally advanced or the metastatic ones, it may become less than 3% [1,8,16,37]. For a better outcome of this catastrophic tumour, it should be diagnosed early and treated through multidisciplinary teams of surgeons, gastroenterologists/interventional upper endoscopists, medical/radiation oncologists, diagnostic/intervention [16].…”
Section: Treatment Of Pdacmentioning
confidence: 99%
“…They play crucial post-transcriptional regulatory roles in the pathogenesis of various diseases, particularly cancers. 16 19 There is a growing consensus suggesting that circRNAs also have crucial regulatory functions in DR development and could serve as potential markers for diagnosing and treating DR. 20 22 Several circRNAs, such as CircDNMT3B, cZNF609, and CircHIPK3, have been implicated in retinal vascular dysfunction in a diabetic environment. 21 In a previous research, we documented hsa_circ_0001953 is upregulated in cases of proliferative DR (PDR) and has huge prospects for early diagnosis of this disease.…”
Section: Introductionmentioning
confidence: 99%